The Effect of the Spanish Reconquest on Iberian Cities - David Cuberes; Rafael González-Val (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper studies the effect of the Spanish Reconquest, a military campaign that aimed to expel the Muslims from the Iberian Peninsula, on the population of its most important cities. The almost four centuries of Reconquest offer a “quasi-natural” experiment to study the persistence of population shocks at the city level. Using a generalized difference in differences approach, we find that the Reconquest had an average significant negative effect on the relative population of the main Iberian cities even after controlling for a large set of country and city-specific geographical and economic indicators, as well as city-specific time trends. Nevertheless, our results show that this negative shock was short-lived, vanishing within the first one hundred years after the onset of the Reconquest. These results can be interpreted as weak evidence on the negative effect that war and conflict have on urban primacy. They also suggest that the locational fundamentals that determined the relative size of Iberian cities before the Reconquest were more important determinants of the fate of these cities than the direct negative impact that the Reconquest had on their population.
Keywords: R12; N9; 330; Locational Fundamentals; City Growth; Lock-in Effects; Warfare and Cities